Adaptability of Digital Reference Searches for Islamic Higher Education Students in Central Java, Indonesia - Anisa Listiana; Abdul Fatah (Universitas Pendidikan Ganesha, 2024)
Islamic university students face challenges in searching for digital references, particularly in utilizing available e-resources, both online and in university libraries. A lack of digital literacy skills, especially in accessing Arabic-language sources, poses a significant obstacle to their academic progress. This study aims to analyze the level of digital literacy skills among Islamic university students in finding digital references and to identify the challenges they encounter. This research employs a quantitative approach with a descriptive method. Data were collected through questionnaires, observations, and document analysis. The study population consists of Islamic university students, with validity testing conducted using the Pearson product-moment formula and reliability testing using Cronbach’s alpha. The findings indicate that students' digital literacy skills in utilizing e-resources are relatively high, with an average total score of 3.25 on a 0.8 scale. This score falls within the moderate category (2.6–3.4). Nevertheless, significant challenges remain in utilizing digital references, particularly in Arabic-language materials, highlighting the need for university policies to enhance students' digital literacy skills, particularly in religious faculties. The study concludes that strengthening digital literacy strategies is essential for improving access to and utilization of academic references in Islamic higher education institutions.